An assessment of the archives practices in the Philippine provinces of the Society of the Divine Word (SVD), 1909-2009 - Araceli, Alfonso A. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
For the many years that Society of the Divine Word (SVD) congregation has been engaged in missionary work in the Philippines, little has been known that an effort in archiving is exerted. There were attempts in the past to organize and to put in order the records and filing system of the congregation but it did not succeed. Being the oldest in the three Philippine provinces, the PHC Archives has the most collection of documents in the congregation, aside from books and few artifacts that it has at present.